COMPARING THE COMMUNICATION METHODS IN IRAQI CONSTRUCTION PROJECTS DURING THE IMPLEMENTATION STAGE - Hatem, Wadhah Amer; Al-Tmeemy, Samiaah M. Hassen (Basrah Journal for Engineering Sciences, 2014)
Construction projects are complex projects and their organisations are characterised by a high degree of fragmentation since they are distributed in large areas and clearly they involves of many activities, each one being divided into sub-activities and so on. Hear clear and good communication between projects stakeholders leads to the project being more successful in contrast to when the communication is weak. This paper compares two methods of communication used in Iraqi construction projects during the implementation stage, namely the Face to Face (FTF) approach which is characterised as expensive and disruptive and Computer Mediated Communication (CMC) which represents the modern method in the communication field. The results show that the CMC method is more productive and economic than FTF and takes less time when completing an implementation work; in addition, the people are less affected by emotional factors in the construction project in contrast to FTF.